Phycoremediation of Synthetic Dyes: An Effective and Eco-Friendly Algal Technology for the Dye Abatement - Abate Ayele; Deribe Getachew; M. Kamaraj; A. Suresh (Journal of Chemistry)
Rapid industrialization leads to serious environmental hazards due to the increase in the release of pollutants into the environment. Industries that use synthetic dyes for different applications are a predominant source for dye contaminants by releasing the dye in wastewater with pretreatment or without treatment directly into the water bodies, making serious water pollution in the environment. Therefore, it is imperative to safeguard the environment from such contaminants and their associated negative impacts. The conventional treatment method that is used to treat dye-contaminated wastewater is generally costly and has a possibility to produce secondary metabolites. Due to the above problems, the biological method is preferable to treat effluent or dye-contaminated wastewater. Phycoremediation is an algae-based eco-friendly dye abatement technique from contaminated environments. This review highlights the phycoremediation of dyes and its underlying mechanisms along with the information on synthetic dyes, classification, hazardous effects, and other major techniques of dye abatement. This review provides a comprehensive insight into several influencing factors such as pH, temperature, contact time, the dose of algae biomass, and agitation speed, as well as functional groups involved in the phycoremediation process.